A System Dynamic Model for Sustainable Construction and Demolition Waste Recycling in Libya - Itad Shiboub; Gabriel J. Assaf (European Scientific Journal, ESJ, 2019)
In Libya, Construction and Demolition Waste materials (C&DW) are currently thrown in landfills or illegally dumped. In regions where the C&DW is not landfilled, insufficient C&DW management fails to take advantage of the full value of the materials that could be repurposed for road construction. This research aims to develop a sustainable C&DW management model appropriate to Libya and similar countries. Over 97% of construction in Libya uses cement; therefore, this study focuses on cement production and consumption and creates a simulation to model the parts of the construction industry. This study uses System Dynamics (SD), which is a tool used by stakeholders in policy planning to make better decisions about how to manage C&DW. This study models and predicts C&DW from 2008 until 2030, taking material cost, availability, recyclability and environmental, economic and social impacts into account. The model conforms to historical data from 2008 to 2016 and then becomes a predictive model until 2030; the years following 2011 are particularly critical due to the amount of destruction and the resulting rebuilding. The model shows that having a higher collection budget does not result in better environmental outcomes unless there is money allocated for C&DW recycling. The study quantifies the amount of material in Libya generated from demolition that is not reused; this data becomes a means of analyzing the value of the waste. The model output provides important data (e.g., cement consumption, GDP) for future resource management.